Electronic structure modulation in Prussian blue and its analogs: Progress and challenges in perspective of energy-related catalysis - Singh B.; Arya Y.; Lahiri G.K.; Indra A. (My University, 2025)
Prussian blue, a more than three hundred years old inorganic coordination polymer, has drawn immense interest in the field of energy conversion. Prussian blue (PB) and Prussian blue analogs (PBAs) have been extensively used for water oxidation, hydrogen evolution, oxygen reduction, nitrogen reduction reaction, etc. In addition, PB and PBAs were explored as the cocatalysts for photocatalytic and photoelectrochemical energy conversion processes. Although initial studies focused on the development of morphology, porosity, surface area, accessible catalytic sites, core-shell structure, etc., the tuning of the electronic structure was found to largely influence the electrochemical features of PB and PBAs. The inter-valence charge transport in PB and PBAs through the –CN bridge can also be modulated by altering the electronic structure of the metal sites. This, in turn, offers a significant modification of its properties as a cocatalyst when combined with a semiconductor. The present review article addresses the effect of electronic structural modulation in PB and PBAs to improve its electrocatalytic and cocatalytic activities. The recent achievements and challenges in designing PBAs and their application in energy conversion have been highlighted along with potential future advancements. Special emphasis has been given to understanding structural aspects and the subsequent establishment of a structure-activity relationship for energy conversion processes. © 2024 Elsevier B.V.